Analysis of Consumer Satisfaction Using Delivery Service “Titipan Kilat” (TIKI) - T. Nurhaida; Lilinesia Lilinesia; Amrin Mulia Utama (Budapest International Research and Critics University, 2021)
The delivery service business is needed and influential in the daily activities of consumers. Many companies run this business so that consumers have many alternatives and can choose a reliable courier service, provide the best service, as well as customer satisfaction. Consumer satisfaction itself is formed, among others, from service quality and trust in the company. are associative and quantitative approaches. The population in this study is TIKI consumers who have used TIKI services more than three times. After testing the hypothesis, the results show that the service quality variable is in the form of completeness (facilities and infrastructure), paying attention to customer desires, always on time in providing services, responsive in solve problems and always carry out their duties to increase customer satisfaction and trust variables Always be honest in doing work,, always fulfill their responsibilities to customers, provide the best quality service compared to competitors, and always strive to be the best delivery of goods among others is the best way foster consumer confidence using express delivery services.”Titipan Kilat”(TIKI).